Incidence and neuropsychological sequelae of head injury in a New Zealand adolescent sample : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Arts in Psychology at Massey University - Body, Catherine May (Massey University, 1995)
The purpose of this study was to determine if there were head-injured students experiencing difficulties that were not being recognised by parents and teachers alike. The study involved two parts. The first part involved a survey of all fourth formers at Awatapu College in Palmerston North, New Zealand, and was concerned with obtaining information regarding incidence, etiology, and awareness of head injury. The second part of the study examined a proportion of students who reported ongoing problems of the kind common after a head injury in more detail. Information was obtained through a self-report questionnaire, neuropsychological measures, a teacher rating form and a parent rating form. The results yielded a incident rate of nearly 14% which is substantially higher than that reported by previous studies, and the results also suggest that head-injured students are more aware of common symptomatology following head injury in comparison to non head-injured students. Apart from on Trial 5 and 6 of the AVLT, there was no significant difference between the head-injured and control groups on the neuropsychological measures. With regards to behavioural and cognitive difficulties that the students may be experiencing, there was a low level of agreement between students, teachers and parents.
Keywords: Brain-damaged children; Head wounds and injuries; Psychology